The significance of immunonutrition nutritional support in patients undergoing postoperative adjuvant chemotherapy for lung cancer: case–control study - Tevfik Ilker Akcam; Ahmet Kayahan Tekneci; Onder Kavurmaci; Ali Ozdil; Ayse Gul Ergonul; Kutsal Turhan; Alpaslan Cakan; Ufuk Cagirici (World Journal of Surgical Oncology, 2023)
Abstract Background In this study, the effect of postoperative early nutritional supplementation on the course of the disease was investigated in patients who were operated for non-small cell lung cancer and received adjuvant chemotherapy. Methods The study examined the data of patients who anatomical pulmonary resection for non-small cell lung cancer and who were treated with adjuvant chemotherapy at our clinic between January 2014 and January 2020. Patients who received early postoperative nutritional supplements and those who continued with a normal diet were compared in terms of complications, mortality, recurrence, and survival. Results The study sample consisted of 68 (84%) male and 13 (16%) female patients, and the mean duration of postoperative follow-up was 31.6 ± 17.9 (4–75) months. Metastasis was identified in eight (17.4%) patients in GrupNS (Nutritional Supplements) compared to 10 (28.6%) patients in GroupC (Control) (p = 0.231). Of the total, 11 (23.9%) patients died in GroupNS compared to 13 (37.1%) in GroupC (p = 0.196). Mean survival was 58.9 ± 3.8 (95% CI: 4.0–75.0) months in GroupNS compared to 43.5 ± 4.6 (95% CI: 6.0–66.0) months in GroupC (p = 0.045). Conclusion Early nutritional supplements should be considered as having a positive effect especially on survival in this specific patient group involving factors with high catabolic effects, such as neoplasia, operation, and chemotherapy together.